PENERAPAN PENDIDIKAN KARAKTER K.H. AHMAD DAHLAN PADA PELAJARAN SEJARAH - Heryati Heryati; Ruslan Ruslan; Wendy Anugrah Octavian; Dewi Setyawati (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study aims to understand the implementation process and the students' perceptions and responses to the character education of K.H. Ahmad Dahlan in the History subject for Grade X at SMA Aisyiyah 1 Palembang. This qualitative research incorporates geographical, sociological, anthropological, and educational approaches. The type of research is descriptive qualitative. The conclusions of this study are: (1) the implementation of this character education is carried out by the teacher preparing a lesson plan (RPP) and syllabus in advance, where in every material, the teacher consistently integrates K.H. Ahmad Dahlan's character education through the learning process, starting from the opening activity, the main learning activity, the closing activity, and the evaluation. (2) The obstacles to character education in SMA Aisyiyah 1 Palembang include several factors: time, media, environment, and teaching models. On the other hand, the supporting factors for this character education are facilities, media, and teaching models. (3) Students' perceptions and responses to this character education are positive, as seen in their enthusiasm for learning, from the opening and main learning activities to the closing activities.